Eating attitudes in a group of 11-year-old urban South African girls - Petersen, Carmen D (2006)
OBJECTIVES: To explore and describe eating attitudes in early pubertal 11-year-old black and white South African girls in an urban environment undergoing transition. DESIGN: The study was designed as a cross-sectional baseline initiative within a longitudinal study. SUBJECTS: Two hundred and two subjects were randomly selected; 54 were white and 148 black. METHODS: Subjects completed questionnaires, and anthropometric measurements were taken. OUTCOME MEASURES: Variables included body mass index (BMI), eating attitudes (EAT score), dietary intake, socio-economic status, pubertal status and level of physical activity. RESULTS: As expected, the prevalence rate of abnormal eating attitudes in this group of girls was low (1%). No significant ethnic differences were found in the total EAT scores. White participants displayed greater oral control, while their black peers displayed greater tendencies toward dieting (p = 0.05). Girls who scored higher on the dieting subscale had a larger body size and were more inactive than low dieting scorers (p = 0.05). A relationship between body size measurements and dietary intake was found only in black girls. Traditionally a larger figure is accepted in black culture. However our data suggest a move away from this, indicating acculturation, as awareness of increased body size significantly influenced dieting attitudes. However, scores were within the normal range. CONCLUSIONS: There is early evidence suggesting the impact of societal transition on young black girls with regard to eating attitudes. Black girls in this age group are adopting Western ideals of beauty and thinness.